Learning Communication in Tahfidz Quran Through Tarkiz Method - Rina, Nofha (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
This study aims to examine how the learning in Tahfidz Quran through the Tarkiz method. The researcher also analyzed the implementation of the Tarkiz method in learning tahfidz Quran by students, teachers, and Tarkiz’s coordinator. This research is qualitative with a case study approach in revealing Tarkiz's learning communication because social, cultural, and human behavior phenomena are not enough to record things that appear real. Therefore, they must also be examined in the context behind them. The results obtained in this study are in the form of a Welas Asih communication model in tahfidz Quran that can build commitment in human relations so that an educative interaction learning can be realized.